The Role of the Nurse Unit Manager Function on Nursing Work Performance: A Systematic Review - Fitriyanti Patarru'; Basilius Yosepfus Weu; Febrina Secsaria Handini; Heryyanoor Heryyanoor (Universitas Airlangga, 2019)
Introduction: The role of Nurse Unit Manager is to improve the nurses’ performance in the context of their professional services. This role consists of planning, organizing, actuating and controlling. The aim of this systematic review was to determine the influence of the nurse unit manager’s management functions related to the nurses’ performance.Methods: The literature search was conducted in the PubMed, Scopus, ProQuest, Science Direct and SAGE databases with the keywords ‘head nurses’, ‘management function’ and ‘nurse performance’. The articles were reviewed using the inclusion criteria, which was that the title and abstract was in accordance with the desired topic, that the article aimed to analyze the influence of the nurse unit manager’s management functions related to the nurses’ performance and that it was explained in English. The exclusion criteria were that the title, abstract and purpose of the article was not in accordance with the topic of focus. The search identified 15 relevant journals from the 276.303 articles published between 2014 and 2019.Results: The results indicate a significant relationship exists between the role of the nurse unit manager and nursing work performance.Conclusion: To improve the management function of the nurse unit manager, it is necessary to conduct training for the nurse unit manager to allow them to better understand the functions and role of the nurse unit manager.